The use of a collaborative structured methodology for the development of a multifaceted intervention programme for the management of asthma (the MIA project), tailored to the needs of children and families of South Asian origin: a community-based, participatory study - Monica Lakhanpaul; Deborah Bird; Lorraine Culley; Nicky Hudson; Noelle Robertson; Narynder Johal; Melanie McFeeters; Charlotte Hamlyn-Williams; Mark Johnson (National Institute for Health Research, 2014)
Background: Asthma is one of the most common chronic childhood illnesses in the UK. South Asian children are more likely to suffer from their asthma and be admitted to hospital. While this inequality needs to be addressed, standard behaviour-change interventions are known to be less successful in minority ethnic groups. Evidence suggests a need to enhance services provided to ethnic minority communities by developing culturally sensitive tailored interventions. Objectives: The Management and Interventions for Asthma (MIA) project aimed to test an iterative multiphase participatory approach to intervention development underpinned by the socioecological model of health, producing an intervention-planning framework and enhancing an evidence-based understanding of asthma management in South Asian and White British children. Design: Interviews and focus groups facilitated by community facilitators (CFs) were used to explore knowledge and perceptions of asthma among South Asian communities, children, families and healthcare professionals (HCPs). A smaller comparison group of White British families was recruited to identify aspects of asthma management that could be addressed either by generic interventions or by a tailored approach. Collaborative workshops were held to develop an intervention planning framework and to prioritise an aspect of asthma management that would be used as an exemplar for the development of the tailored, multifaceted asthma intervention programme. Setting: The community study was based in a largely urban environment in Leicester, UK. Participants: Participants were recruited directly from the South Asian (Indian, Pakistani and Bangladeshi) and White British communities, and through the NHS. Children were aged between 4 and 12 years, with a range of asthma severity. Intervention development: The study had four phases. Phase 1 consisted of an evidence review of barriers and facilitators to asthma management in South Asian children. Phase 2 explored lay understandings of childhood asthma and its management among South Asian community members (n = 63). Phase 3 explored perceptions and experiences of asthma management among South Asian (n = 82) and White British families (n = 31) and HCP perspectives (n = 37). Using a modified intervention mapping approach incorporating psychological theory, phase 4 developed an intervention planning framework addressing the whole asthma pathway leading to the development of an exemplar multifaceted, integrated intervention programme called 'ACT [Awareness, Context (cultural and organisational) and Training] on Asthma'. Results: Data on the social patterning of perceptions of asthma and a lack of alignment between the organisation of health services, and the priorities and competencies of British South Asian communities and families were produced. Eleven key problem areas along the asthma pathway were identified. A four-arm multifaceted tailored programme, 'ACT on Asthma', was developed, focusing on the theme 'getting a diagnosis'. This theme was chosen following prioritisation by families during the collaborative workshops, demonstrating the participatory, iterative, phased approach used for the intervention design. Conclusions: The MIA study demonstrated barriers to optimal asthma management in children at the family, provider and healthcare system levels and across the whole asthma pathway. Interventions need to address each of these levels to be effective. Minority ethnic communities can be successfully engaged in collaborative intervention development with a community-focused and culturally sensitive methodology. Future work: Further research is required to (1) assess the feasibility and effectiveness of the proposed 'ACT on Asthma' programme, (2) develop methods to increase active participation of children in research and service development, (3) develop and test strategies to enhance public understanding of asthma in South Asian communities and (4) identify effective means of engaging the wider family in optimising asthma management. Funding: The National Institute for Health Research Health Services and Delivery Research programme.